1996
DOI: 10.1093/jee/89.6.1638
|View full text |Cite
|
Sign up to set email alerts
|

High-Power Microwave Radiation as an Alternative Insect Control Method for Stored Products

Abstract: Insect mortality studies were performed with a high-power microwave source operating at a frequency of 10.6 GHz at power levels of 9-20 kW to irradiate samples of soft wite wheat, Triticum aestivum (L.), infested with maize weevil, Sitophilus zeamais Motschul-sky, and ground wheat infested with red flour beetle, Tribolium castaneum (Herbst). These pests are common internal and external feeders in stored products, respectively. Samples at various age intervals from egg to adult were exposed. The results support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 1 publication
3
14
0
Order By: Relevance
“…To meet phytosanitary and quarantine regulations for international trade, there is an urgent need in developing nonchemical postharvest pest control methods for dry soybeans. Radio frequency (RF) energy is an electromagnetic wave with a frequency of 1e300 MHz, which provides rapid and volumetric heating, and has been studied as a non-chemical alternative for postharvest insect control in dry products (Halverson, Burkholder, Bigelow, Nordheim, & Misenheimer, 1996;Nelson, 1973;Tang, Ikediala, Wang, Hansen, & Cavalieri, 2000), such as alfalfa seed (Yang, Zhao, & Wells, 2003), grain (Nelson, 1996), legume (Jiao, Tang, Johnson, Tiwari, & Wang, 2011;Wang, Tiwari, Jiao, Johnson, & Tang, 2010), lentil (Jiao, Johnson, Tang, & Wang, 2012), rice (Lagunas-Solar et al, 2007;Zhao, Qiu, Xiong, & Cheng, 2007), walnut (Mitcham et al, 2004;Wang et al, 2001;Wang, Monzon, Johnson, Mitcham, & Tang, 2007a, b;Wang et al, 2006), and wheat (Halverson et al, 1996). The relatively long wavelength of RF usually results in deep penetration depth and predictable temperature profiles in foods, but the nonuniform heating is still a problem for RF heating technology to be applicable in the food industry (Tang et al, 2000;Wang et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…To meet phytosanitary and quarantine regulations for international trade, there is an urgent need in developing nonchemical postharvest pest control methods for dry soybeans. Radio frequency (RF) energy is an electromagnetic wave with a frequency of 1e300 MHz, which provides rapid and volumetric heating, and has been studied as a non-chemical alternative for postharvest insect control in dry products (Halverson, Burkholder, Bigelow, Nordheim, & Misenheimer, 1996;Nelson, 1973;Tang, Ikediala, Wang, Hansen, & Cavalieri, 2000), such as alfalfa seed (Yang, Zhao, & Wells, 2003), grain (Nelson, 1996), legume (Jiao, Tang, Johnson, Tiwari, & Wang, 2011;Wang, Tiwari, Jiao, Johnson, & Tang, 2010), lentil (Jiao, Johnson, Tang, & Wang, 2012), rice (Lagunas-Solar et al, 2007;Zhao, Qiu, Xiong, & Cheng, 2007), walnut (Mitcham et al, 2004;Wang et al, 2001;Wang, Monzon, Johnson, Mitcham, & Tang, 2007a, b;Wang et al, 2006), and wheat (Halverson et al, 1996). The relatively long wavelength of RF usually results in deep penetration depth and predictable temperature profiles in foods, but the nonuniform heating is still a problem for RF heating technology to be applicable in the food industry (Tang et al, 2000;Wang et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%
“…Radio frequency (RF) and microwave (MW) treatments have been studied as a non-chemical alternative for postharvest insect control in dried agricultural commodities, such as grain (Nelson, 1996), rice (Lagunas-Solar et al, 2007;Zhao, Qiu, Xiong, & Cheng, 2007), walnut (Wang, Monzon, Johnson, Mitcham, & Tang, 2007a, 2007b, and wheat (Halverson, Burkholder, Bigelow, Nordheim, & Misenheimer, 1996). To develop potential phytosanitary RF and MW thermal treatments for legumes, it is important to determine the dielectric properties that govern the interaction between the electromagnetic energy and the legumes.…”
Section: Introductionmentioning
confidence: 99%
“…Shayesteh and Barthakur (1996) reported that intermittent power supply is more effective in killing insects and thus the operational cost of microwave generator could also be minimized. Halverson et al (1996) studied the mortality of S. zeamais and T. castaneum in wheat by microwave treatment at a frequency of 10600 MHz at a power level of 9-20 kW. Mortalities of ≥93 % and ≥94 % were obtained for S. zeamais and T. castaneum, respectively.…”
Section: Insect Mortalitymentioning
confidence: 99%